2009
DOI: 10.1002/jobm.200900089
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new biosurfactant produced by Trichosporon montevideense CLOA 72 isolated from dairy industry effluents

Abstract: The yeast strain CLOA 72 isolated from the effluent of a dairy industry in Brazil and identified as Trichosporon montevideense, was able to grow and produce a glycolipid biosurfactant when cultured on a mineral medium (MM) with sunflower oil as the carbon source. Biosurfactant production was partially growth-associated and maximal emulsification activity was observed at 144 h of cultivation (78.92%). The biosurfactant purified by precipitation with ethanol showed 78.66% emulsifying activity when used in concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 36 publications
1
22
0
6
Order By: Relevance
“…These characteristics indicated that rhamnolipids were potential candidate for use in bioremediation of hydrocarbon-contaminated sites or in the petroleum industry a conclusion that was also confirmed by (Perfumo et al 2010). (Monteiro et al 2009) reported the growth and biosurfactant production using sunflower oil supplemented mineral medium by the yeast Trichosporon montevideense , CLOA 72. The glycolipid produced exhibited good surface and emulsifying activity with vegetable oils, toluene, kerosene, isooctane, cyclohexane, hexane, diesel oil and hexadecane.…”
Section: Biosurfactant Production Using Single Substrate Of Vegetablementioning
confidence: 99%
“…These characteristics indicated that rhamnolipids were potential candidate for use in bioremediation of hydrocarbon-contaminated sites or in the petroleum industry a conclusion that was also confirmed by (Perfumo et al 2010). (Monteiro et al 2009) reported the growth and biosurfactant production using sunflower oil supplemented mineral medium by the yeast Trichosporon montevideense , CLOA 72. The glycolipid produced exhibited good surface and emulsifying activity with vegetable oils, toluene, kerosene, isooctane, cyclohexane, hexane, diesel oil and hexadecane.…”
Section: Biosurfactant Production Using Single Substrate Of Vegetablementioning
confidence: 99%
“…They are primarily produced by fermentation with renewable carbon sources, such as vegetable oils (Costa et al, 2006). Some cheaper raw materials and recycling substrates from agricultural operations, food processing and other industrial processes could be used for cost-effective biosurfactant production (Makkar and Cameotra, 2002; Nitschke et al, 2005, 2009; Monteiro et al, 2009). Their environmental compatibility, effectiveness at extremes of temperature, pH and salinity, and high specificity to targeted pathogens (Haba et al, 2000; Rivardo et al, 2009) make these biosurfactants attractive and desirable for widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…The compound 2, (2E)-1-(4´-hydroxy-2´,6´-dimethoxy-3´,5´-dimethylphenyl)-3-phenylprop-2-en-1-one, showed similar structure to 1, seems to be an unedited substance. The compounds 3-4, isolated as pale yellow solids, were elucidated by means of NMR data, hydrolysis, peracetylation and GC/MS analysis (Cota et al, 2008;Monteiro et al,2009;Monteiro et al, 2010). It was possible to confirm the identity of the sugar moiety as rhamnose for 3 (Figure 1) and arabinose for 4 (Figure 2).…”
Section: Cytotoxicity Assays With Human Cancer Cell Lineagesmentioning
confidence: 96%